Sarong and Peci in Santri Tradition: Frithjof Schuon's Perennial Philosophy Perspective - Farid; Savira, Annisa Ghina; Nurani, Shinta; Khasri, M. Rodinal Khair (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
In the context of Indonesia and several regions in Asia, including Africa, the sarung and peci play a significant role as cultural artifacts with both material and non-material value. This research explores the correlation between the sarung and peci with forming individual and collective identities, particularly within religious communities, such as the santri. Through a perennial philosophy approach, we analyze the role of religion in the cultural acculturation process among the santri. The study results indicate that the sarung and peci are symbols of religious expression and shape a collective identity that encompasses both esoteric and exoteric aspects. Additionally, there is a dualism in the symbolic structure built through the cultural acculturation of the santri, where the sarung and peci become symbolic representations of moral transcendence that distinguish them from the general populace